Myofibrillar structural changes caused by marination with calcium phosphate or calcium chloride and sodium pyrophosphate - T.E. Lawrence; A.T. Waylan; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 2002)
Ultrastructural changes were studied in beef eye of round muscle after 120 hours marination in 0.5, 0.75, or 1.0% calcium phosphate (CaPO) or 2, 4, or 6% calcium chloride or 1% sodium pyrophosphate (CaCl+NaPO) solutions. Increasing the concentration of CaPO caused decreasing myofibril width and increasing myofilament degradation. Increasing the concentration of CaCl+NaPO caused increasing loss of I-band material. Marination of beef eye of round muscle in calcium phosphate or calcium chloride + sodium pyrophosphate solutions caused denaturation of myofibrillar proteins likely due to marinating solution acidity.
Keywords: Cattlemen' s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Marinades; Muscle structure